Examining SGIDs through a disability lens: Increasing awareness and access in a CTL program - Daisy L. Breneman; Emily Gravett (To Improve the Academy)
Centers for teaching and learning (CTLs) have increasingly been attending to diversity, equity, inclusion, justice, and access (DEIJA), offering myriad programs for instructors to learn how to make their teaching more welcoming and effective for all students. Yet considerations of disability continue to lag behind in higher education, and educational developers themselves may not always create programs that are inclusive and accessible. In this article, we will focus on one popular CTL program, primarily called Small-Group Instructional Diagnosis (SGID) in the literature. When we examine this program through the lens of Disability Studies, we begin to realize just how much ableism permeates its design and implementation. This article will begin an important process of uncovering, naming, and detailing some of the overlapping barriers for those involved in the SGID process and the accompanying equity and access gap(s) that may inadvertently be created because SGIDs are so frequently offered across the United States. We will explore how we might respond to some of the limitations of the SGID program, as currently and commonly conceived, including turning to Universal Design for Learning (UDL) for redesign ideas and even considering whether this program continues to be the best way to achieve its intended outcomes. We offer a model for more broadly rethinking educational development processes that may perpetuate ableism and intersecting forms of oppression.